Badania nad Niektórymi Typami Niesinusoidalnych Widm Naprężeń Zmęczeniowych - M. Zakrzewski; T. Porębski (Engineering Transactions)
The aim of the experimental part of this work was to verify the assumption that the role of the tensile and compressive stresses in a fatigue load cycle is not the same. Four series of experiments were carried out by loading test-pieces having the same dimensions and made of the same material by different load spectra. Two of the four load spectra applied were of the biharmonic type and differed from each other by the relative duration of the compressive and tensile load in the load cycle. The above assumption has been verified by the tests which have shown that with increasing relative duration of the tensile load the strength decreases. The value of the stresses was so chosen that the fatigue rupture took place after 105-105 cycles that is the tests were carried out in the range of limited fatigue strength. This was justified by the conditions of motion of the pulsator for experiments concerning the behaviour of metals loaded with biharmonic load spectra of which the prototype has been constructed at the Laboratory of Strength of Materials of the Technical University of Wroclaw. This device enables us practically to obtain any type of biharmonic load, there being a free choice of sinusoidal components. The results discussed constitute a fragment of a greater program of investigations of the influence of the form of the load spectrum on the fatigue strength, which is now in the course of being realized at the Laboratory of Strength of Materials of the Technical University of Wrocław.